(untitled) (Proceedings of International Conference on Special Education, 2023)
One of the challenges of grade 10 students is what track to choose in senior high school years. As identified in most of the studies, different factors influence grade 10 learners’ decisions on which senior high school track they ought to pursue, which include personal interest, family influence, peer influence, job opportunities, and financial condition. Embracing the realization of inclusion, learners with special educational needs (LSENs) also experiencing this kind of predicament, the school should be prepared with what support and program they can offer to their learners who are categorized as LSENs for them to choose and decide what senior high school track will they pursue. The purpose of this study is to determine what factors influenced the senior high school track preferences of grade 10 learners with disabilities (LWDs) in a public high school in Cavite, Philippines, and also to know if the health condition of the participants greatly influenced their decision in choosing the senior high school track. In this study, a descriptive design was used, along with a four (4) point Likert scale for each indicator. The grade 10 LWDs of an inclusive public high school in Cavite, Philippines served as participants, and through an online survey questionnaire data was gathered. Data was then interpreted using frequency, ranking, and weighted mean. This study revealed that the LSENs’ interests were the most influential factor in their choice of senior high school track while peer influence was the least.